2015
DOI: 10.1080/14786419.2014.996148
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial evaluation of the essential oils of Bocageopsis pleiosperma Maas

Abstract: Essential oils from the leaves, twigs and barks of Bocageopsis pleiosperma Maas were obtained by using hydrodistillation and analysed by using gas chromatography coupled to mass spectrometry. Several compounds (51) were detected and identified, being β-bisabolene the main component in all aerial parts of the plant, with higher concentration in the leaves (55.77%), followed by barks (38.53%) and twigs (34.37%). In order to increase the biological knowledge about the essential oil of Bocageopsis species, antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Antibacterial activity of essential oils of Tripleurospermum disciforme was reported that the reason for higher antibacterial effect is the presence of β-farnesene and β-sesquiphellandrene [23]. The essential oils of Bocageopsis pleiosperma Maas rich in β-bisabolene were reported to have high antifungal activities [24]. Their results are consistent with ours.…”
Section: Resultssupporting
confidence: 83%
“…Antibacterial activity of essential oils of Tripleurospermum disciforme was reported that the reason for higher antibacterial effect is the presence of β-farnesene and β-sesquiphellandrene [23]. The essential oils of Bocageopsis pleiosperma Maas rich in β-bisabolene were reported to have high antifungal activities [24]. Their results are consistent with ours.…”
Section: Resultssupporting
confidence: 83%
“…The antimicrobial activities of EOs from the leaves, branches, and bark of Bocageopsis pleiosperma were evaluated. The EOs obtained from the bark had a moderate effect against Staphylococcus epidermidis (MIC = 250 µg•mL −1 ), while the other EOs did not show antimicrobial activity [58].…”
Section: Antimicrobian Activitymentioning
confidence: 92%
“…Bauhinia ungulata (leaves) Fabaceae HD (E)-caryophyllene (15.9%), caryophyllene oxide (9.2%) α-humulene (8.1%) and epi-γ-eudesmol (7.5%) [21] Bocageopsis pleiosperma (Barks) Annonaceae HD β-bisabolene (38.53%), δ-cadinene (7.55%), β-selinene (6.46%) and α-selinene (5.18%) [22] B. pleiosperma (leaves) Annonaceae HD β-bisabolene (55.77%), (E)-α-bergamotene (6.94%) and β-farnesene (E) (6.05%) [22] B. pleiosperma (twigs) Annonaceae HD β-bisabolene (34.37%), cryptomerione (9,60%) and (2Z, 6Z)-farnesol (7,20%), [22] B. multiflora (Leaves) Annonaceae HD spathulenol (20.30%) and β-bisabolene (11.90%) [23] B. multiflora (Aerial parts) Annonaceae HD cis-linalool oxide (33.10%) and 1-epi-cubenol (16.60%).…”
Section: Species Family Extraction Methods Compounds Referencesmentioning
confidence: 99%
“…The chemical profile of essential oils from species of the Annonaceae family showed hydrocarbon and oxygenated sesquiterpenes as the main constituents, where the compounds β-bisabolene (55.77%), caryophyllene oxide (55.70%), and β-eudesmol (51.92%), were respectively dominant in the essential oils of Bocageopsis pleiosperma [ 22 ], Guatteria blepharophylla [ 23 ], and G. friesiana [ 35 ]. However, it was possible to observe other types of chemical classes in the genus Anonnace-ae, such as the oxygenated monoterpene cis -linalool oxide (33.10%) in the essential oil of Bocageopsis multiflora [ 24 ] and the alcohol 4-heptanol (33.80%) in the essential oil of Duguetia quitarensis [ 24 ].…”
Section: Chemical Composition Of the Essential Oils Of The Amazonmentioning
confidence: 99%